Activity and Consciousness (Revista Dialectus - Revista de Filosofia, 2016)
Published in Russian in the journal Voprosyfilosofii, n. 12, p. 129-140 (1972) and English in the book Philosophy in the USSR, Problems of Dialectical Materialism (Moscow, 1977, p. 180-202). Available at Marxists Internet Archive [http://www.marxists.org/]. Reproduction Rights: licensed under a Creative Commons License.